Conceptualization of Ukraine's foreign policy choice as a marker of democratization - Amirov, Artur O.; Аміров, Aртур Олександрович; Аміров, А. О. (Czestochowa, 2022)
The purpose of the article is to conceptualize foreign policy choice as one of the markers of the democratization of political institutions in Ukraine. Special attention is focused on the connection between the democratization of political institutions and Ukraine's foreign policy choice. The choice between democracy and authoritarianism is not only a matter of internal transformation. It covers the foreign policy space as well. Ukraine has chosen the path of European and Euro-Atlantic integration. The implementation of this foreign policy choice requires the activation of democratization processes and the expansion of the space for individual freedom of choice. For this reason, the values of freedom of speech and individual rights are noted among the determinants of Ukraine's democratic foreign policy choice. The implementation of the democratic foreign policy choice made by the Ukrainian political class is impossible without effective institutions: free mass media, electoral contests, and parliamentarism. All of them should contribute to political and economic competition and the creation and strengthening of the middle class, which, in fact, should make a democratic political choice. The research used an interdisciplinary approach, which made it possible to determine the differences between existential and marketing choices, between everyday and political choices and substantiate the presence of political, legal, economic, and communicative dimensions of foreign policy choice. The importance of historical prerequisites for foreign policy choice is substantiated.

Метою статті є концептуалізація зовнішньополітичного вибору як одного з маркерів демократизації політичних інститутів в Україні. Особливу увагу зосереджено на зв'язку між демократизацією політичних інститутів і зовнішньополітичним вибором України. Вибір між демократією та авторитаризмом – це не лише питання внутрішньої трансформації. Він охоплює й зовнішньополітичний простір. Україна обрала шлях європейської та євроатлантичної інтеграції. Реалізація цього зовнішньополітичного вибору потребує активізації процесів демократизації та розширення простору індивідуальної свободи вибору. З цієї причини цінності свободи слова та прав особистості відзначаються серед визначальних факторів демократичного зовнішньополітичного вибору України. Реалізація демократичного зовнішньополітичного вибору українського політичного класу неможлива без ефективних інституцій: вільних ЗМІ, виборчої боротьби, парламентаризму. Усі вони мають сприяти політичній та економічній конкуренції та створенню та зміцненню середнього класу, який, власне, має зробити демократичний політичний вибір. У дослідженні використано міждисциплінарний підхід, який дав змогу визначити відмінності між екзистенціальним і маркетинговим вибором, між повсякденним і політичним вибором та обґрунтувати наявність політичного, правового, економічного та комунікативного вимірів зовнішньополітичного вибору. Обґрунтовано важливість історичних передумов зовнішньополітичного вибору.
Amirov A. O. Conceptualization of Ukraine's foreign policy choice as a marker of democratization / A. O. Amirov // Periodyk Naukowy Akademii Polonijnej. – Częstochowa, 2022. – 55 (2022), nr 6. – S. 127-133. DOI https://doi.org/10.23856/5517
Keywords: political choice; foreign policy; political institutions; European integration; political freedoms; політичний вибір; зовнішня політика; політичні інститути; євроінтеграція; політичні свободи; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science